SUSTAINABLE AGRICULTURE CHALLENGES AND ADVANTAGES IN RURAL PROPERTIES - Marmidt , Tamara (Journal of Interdisciplinary Debates, 2021)
The aim of this article was to analyze the perception of Brazilian family farmers on the topic of sustainability in small rural properties. The central issue is how to keep people in the rural environment, stimulating the rational use of natural resources and causing the least possible environmental impact with their production practices without discussing sustainability issues. The problem lies in the sustainability of small rural properties that use family labor, in which the production process, in general, is artisanal and the production scale is small. The theoretical framework contemplates the theme based on the foundations of the new rurality, productive diversification, pluriactivity and multifunctionality. The results indicate that family farmers on small rural properties do not consider the adoption of production practices that rationally use natural resources and/or that cause the least possible environmental impact. The action logic is capitalist, guided by practices that generate enough income to keep family members, reproduced from the practices observed in large rural producers. The theoretical definition of rural sustainability is dissociated from the practice carried out in small rural properties, which are mainly justified by the absence of family labor and the low profitability of productive activities that include productive diversification and the scale of production.